Advancing Sustainability Through Artificial Intelligence: Implications for Firm Value in Indonesia - Mulyana, Dendi; Widyaningsih, Aristanti; Rozali, Rozmita Dewi Yuniarti (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
This research seeks to explore the influence of AI adoption on ESG performance and further assess the mediation effect of ESG performance in the relation between AI adoption and firm value. The research was carried out from 2020 to 2023 on companies in Indonesia, yielding 288 observational data points. A multivariate analysis was performed utilising partial least squares structural equation modelling (PLS-SEM) to assess the hypothesis. The findings from hypothesis testing demonstrate that AI adoption has a significant favourable impact on ESG performance. Similarly, ESG performance significantly enhances firm value. Additionally, the indirect effects analysis reveals that ESG performance effectively mediates the positive relationship between AI adoption and firm value. AI enhances ESG performance by serving as a strategic resource, improving efficiency, and advancing sustainability to meet stakeholder expectations, further enhancing corporate value. This research encourages government support, managerial integration, and standardised policies for AI-driven business sustainability.